La competencia metafórica y la didáctica del español/L2 - Martín-Gascón , Beatriz (Studia Romanica Posnaniensia, 2023)
This study aims to examine the role of metaphor in the process of teaching and learning a second language (L2), more specifically, L2 Spanish. As part of one of the most popular research lines in the field of Ap- plied Linguistics, i.e., L2 teaching and learning, this research is based on a Cognitive Linguistics approach to language. It presents metaphors not as mere stylistic and rhetorical mechanisms, but as critical components of everyday language and fundamental mechanisms of conceptualization of the world (Lakoff & Johnson, 1980). After providing a summary of the literature exploring the relationship between metaphor and L2 pedagogy and learning, focusing on conceptual metaphor theory and metaphorical competence, we will present the results of a case study with intermediate learners. The empirical investigation exam- ines whether their metaphoric competence is enhanced after the intervention and whether there is a relationship between learners’ general metaphorical competence and linguistic competence –comprehension and production– of a complex metaphorical linguistic construction that expresses emotions.